Who Pays for Maritime Security? Burden Sharing and International Legal Constraints in the Strait of Malacca and Indonesian Archipelagic Sea Lanes - Hartanto, Dhimas Rudy; Renmaur, Aldi Giovano (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
The Strait of Malacca and Indonesia's Archipelagic Sea Lanes (ALKI) facilitating approximately 25 percent of global seaborne trade and roughly 80 percent of East Asia's crude oil supply annually. This article develops the concept of asymmetrical maritime governance burden to explain how UNCLOS structurally privileges navigational freedom while consigning disproportionate security responsibilities to littoral developing states, notably Indonesia. Through qualitative method with juridical analysis, empirical examination of maritime incident data, and a comparative study of international chokepoints. The article demonstrates that existing cooperative mechanisms under Article 43 remain institutionally weak, politically fragile, and fiscally inadequate. The article argues that unless UNCLOS's lacuna on burden financing is addressed through a negotiated protocol or binding regional agreement, the structural inequality between littoral states and user states will deepen, threatening long-term navigational security in one of the world's most strategically indispensable waterways.